3 x − 2 2 x + 1 > 2
If the solution set of the inequality above is given by ( a , b ) .
And if the value of a b = n m , where m and n are coprime positive integers, find the value of m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
When you multiply both sides by 3x-2, don't you have to split into cases depending on the sign of 3x-2? You ended up catching it later, but I don't think your second step was valid.
3 x − 2 2 x + 1 > 2
3 x − 2 2 x + 1 − 2 > 0
3 x − 2 2 x + 1 − 6 x + 4 > 0
3 x − 2 5 − 4 x > 0
3 x − 2 4 x − 5 < 0
So ( a , b ) is ( 3 2 , 4 5 ) a b = 6 5
3 x − 2 2 x + 1 > 2
Let's evaluate the following two cases:
Case 1: 3 x − 2 > 0 ⟺ x > 3 2
2 x + 1 > 2 ( 3 x − 2 )
2 x + 1 > 6 x − 4
5 > 4 x
4 5 > x
Hence, our solution in this case:
3 2 < x < 4 5
Case 2: 3 x − 2 < 0 ⟺ x < 3 2
Multiplying by a negative number changes the direction of the inequality to the opposite:
2 x + 1 < 2 ( 3 x − 2 )
2 x + 1 < 6 x − 4
5 < 4 x
4 5 < x
Since x < 3 2 < 4 5 , therefore we don’t have a solution in this case.
This means, that our only solution is:
x ∈ ( 3 2 , 4 5 )
a = 3 2
b = 4 5
a b = 3 2 × 4 5 = 1 2 1 0 = 6 5
Hence m = 5, n = 6 and our solution should be:
m + n = 5 + 6 = 1 1
Problem Loading...
Note Loading...
Set Loading...
3 x − 2 2 x + 1 > 2
⟹ ⎩ ⎪ ⎨ ⎪ ⎧ 2 x + 1 > 2 ( 3 x − 2 ) 2 x + 1 < 2 ( 3 x − 2 ) for 3 x − 2 > 0 for 3 x − 2 < 0 ⟹ x > 3 2 ⟹ x < 3 2 . . . ( 1 ) . . . ( 2 )
( 1 ) : 2 x + 1 4 x ⟹ 3 2 < x > 6 x − 4 < 5 < 4 5 for x > 3 2 A solution.
( 2 ) : 2 x + 1 4 x ⟹ 3 2 > x < 6 x − 4 > 5 > 4 5 for x < 3 2 No solution.
Therefore, 3 2 < x < 4 5 ⟹ a b = 3 2 × 4 5 = 6 5 ⟹ m + n = 5 + 6 = 1 1